Characterisation of discontinuous carbon fibre preforms for automotive applications - Kirupanantham, Giridharan (2013)
The high cost of raw materials, high labour costs and lengthy cycle times have limited the use of conventional ply-based composites in the automotive industry. This thesis seeks to identify the potential of using low cost discontinuous fibre composites (DFCs) for structural applications. Properties of DFCs are governed by the degree of homogeneity of the reinforcement and discontinuities at the fibre ends, which cause stress concentrations; thereby limiting the mechanical performance of the material. This work focuses on material characterisation of laminates moulded from discontinuous carbon fibre preforms manufactured by a robotic spray process. Through the culmination of this work, a suitable design methodology for automotive applications has been identified. Design procedures for aerospace have also been considered.